(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Jack London’s “Martin Eden” offers a profound examination of the dreams, challenges, and disillusionments faced by American youth at the turn of the twentieth century. The central character, Martin Eden, exemplifies the restless ambition and idealism typical of young people striving for self-betterment and upward mobility in an industrial society. His quest for education, cultural sophistication, and literary achievement reflects the broader American dream of self-made success, revealing both the opportunities available and the contradictions embedded within that ideal. Martin’s journey reveals the conflict between personal ambition and societal limitations, particularly the strict class hierarchies and materialistic ideologies prevalent in his time. As a symbolic figure for American youth, he represents the pursuit of personal success while also illustrating the susceptibility to disillusionment when faced with the stark realities of social inequality and the commercialization of art and intellect. Ultimately, Martin’s tragic ending highlights the fragile balance between youthful idealism and the overwhelming pressure of societal expectations. Through Eden’s rise and fall, London critiques the cultural and economic circumstances of his time while capturing the timeless challenges faced by youth in their quest for ambition, identity, and belonging in pursuit of the American dream.